Price Perception Shows Highest Coefficient in FamilyMart Satisfaction Model: Persepsi Harga Menunjukkan Koefisien Tertinggi Dalam Bentuk Kepuasan di FamilyMart - Ditasari, Nurina; Nugroho, Rusdi Hidayat (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: The rapid development of globalization and technology has intensified competition in the modern retail sector, requiring businesses to better understand determinants of consumer satisfaction. Specific Background: Modern retail outlets face challenges in maintaining customer satisfaction, as indicated by fluctuating brand performance and negative consumer feedback associated with service quality, product quality, and price perception. Knowledge Gap: Despite growing competition, limited empirical clarity exists regarding the relative contribution of these three variables within a single retail context experiencing declining consumer evaluations. Aims: This study aims to examine the simultaneous and partial relationships between service quality, product quality, and price perception on consumer satisfaction. Results: Using quantitative analysis with multiple linear regression on 150 respondents, the findings demonstrate that all three variables significantly contribute both jointly and individually to consumer satisfaction, with price perception exhibiting the highest coefficient, followed by service quality and product quality. The model explains 71.8% of the variance in consumer satisfaction. Novelty: This study identifies price perception as the most dominant determinant within the examined model, highlighting its stronger comparative role among key retail attributes. Implications: The results suggest that retail management should prioritize balanced improvements across service, product, and pricing strategies, with particular emphasis on aligning price perception with perceived value to sustain consumer satisfaction. Highlights: Price-related evaluation shows the strongest coefficient within the regression model. Combined variables explain a substantial proportion of variance in satisfaction levels. All examined factors demonstrate statistically significant contributions both jointly and individually. Keywords: Service Quality, Product Quality, Price Perception, Consumer Satisfaction